Relationship between Parenting Stress and Risk of Attention Deficit Hyperactivity Disorder (ADHD) in Elementary School Children - Alma Rossabela Setyanisa; Yunias Setiawati; Irwanto; Izzatul Fithriyah; Satria Arief Prabowo (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorderduring child development with three symptoms which are comprised of inattention, hyperactivity, andimpulsiveness that may persist into adulthood. This condition can be a stressor for parents in performingparenting and may lead into a state of parenting stress. Objective: To analyze the relationship betweenparenting stress and the risk of developing Attention Deficit Hyperactivity Disorder (ADHD) inelementary school children. Methods: This research was conducted in Surabaya from November 2020to January 2021 with respondents consisting of parents of elementary school children who have ADHDrisk and agreed to participate in this study with a total of 55 samples selected using a purposive samplingtechnique. The research design was cross-sectional using demographic questionnaire, AbbreviatedConners Rating Scale (ACRS), and Parenting Stress Index-Short Form (PSI-SF) which were filledout by respondents through an online form. The data were processed and analyzed using One-SampleChi-Square analysis test program with a p-value <0.05, considered statistically significant. Results:The majority of parents experienced moderate parenting stress levels (58.2%). There was a significantrelationship between each level of parenting stress and the risk of ADHD in children (p < 0.001).Conclusions: There is a significant relationship between parenting stress and the risk of ADHD inchildren.